Efektivitas Penggunaan Scilab dalam Pembelajaran Matematika Komputasi di Tingkat Universitas - Asrah Nabila; Yahfizam Yahfizam (Katalis Pendidikan : Jurnal Ilmu Pendidikan dan Matematika, 2025)
The rapid advancement of information technology has driven the adoption of software tools in computational mathematics education, particularly at the university level. One widely utilized software is Scilab, an open-source platform for numerical computation and data visualization. This study aims to evaluate the effectiveness of Scilab in teaching computational mathematics through a literature review methodology. Peer-reviewed articles and research reports related to Scilab, published within the last five years, were systematically analyzed. The findings reveal that Scilab enhances students' grasp of computational mathematics concepts, simplifies the visualization of complex theoretical constructs, and boosts academic achievement. Key challenges in its implementation include instructor preparedness and the necessity for technical training. This study advocates for the integration of Scilab into higher education curricula to support technology-driven pedagogical approaches in computational mathematics.